Inovasi Penanaman Karakter Gotong Royong Berbasis Penguatan Profil Pelajar Pancasila (P5) pada Jenjang Sekolah Dasar - Okpatrioka Okpatrioka; Bermara giri Menur Sari; Naura Zhafirah (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
This research aims to analyze the implementation of the Pancasila Student Profile Strengthening Project (P5) as an effort to strengthen student character, including design; management; processing assessments and reporting results; evaluation and follow-up. This research uses descriptive qualitative methods in Depok state schools in 2022. Data collection techniques include interviews, observation and documentation. Data was analyzed using interactive techniques including data collection, data condensation, data presentation, and conclusion/verification. The research results show that the research results in cultivating the P5-based mutual cooperation character show that (!) the process of implementing the mutual cooperation character during P5 activities begins with diagnostic assessment, introduction, contextualization, real action, reflection-follow-up and celebration of learning. This P5 activity was carried out over a period of 1 week-1 month based on 3 themes (2) strategies given by the teacher to students, namely, a) competition for the themes "entrepreneurship" and "unity in diversity". Through P5 actions, students can strengthen the character dimensions of the Pancasila Student Profile, especially those who are faithful, devoted to God Almighty and have noble character, work together, be independent, have global diversity, reason critically and creatively. Keywords: Innovation, Mutual Cooperation, Character, Project for Strengthening Pancasila Student Profiles